Public opinion of cash transfer for children and adolescents in Costa Rica: Nine out of ten people support greater adequacy - Blofield, Merike (2023)
Child poverty is a multidimensional challenge and decades of evidence show that cash transfers provide simple and effective protection against poverty, especially extreme poverty. A nationally representative survey of the adult population conducted between April and May 2022 in Costa Rica indicates overwhelming public support (90%) for a cash transfer program targeting children and adolescents. In addition, 94% believe that these cash transfers should have at least the same value as the basic food basket, ie. the extreme poverty line. This would imply a value three times the current transfer for primary school students and 1.5 times the average for secondary school students. Regarding coverage, public opinion is divided between those who would restrict transfers to the population in extreme poverty and those who would support broader eligibility.